2023
DOI: 10.3390/nu15061379
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Egg White and Yolk to Infant Diets and Early Childhood Atopic Dermatitis

Abstract: This study investigated whether the introduction of allergenic foods in infancy is associated with atopic dermatitis (AD) in early childhood. Information regarding parental allergic histories, the introduction of six possible allergenic foods (fruits, egg white, egg yolk, fish, shellfish, and peanuts), and physician-diagnosed AD was obtained using age-specific questionnaires (0–2 years). Immunoglobulin E, specific to 20 food allergens, was also quantified at 12 months of age. Logistic regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The initial 1000 days of life play a pivotal role in the development of food allergies, During the period from early pregnancy to childhood, it is essential to prioritize additional observational research and clinical trials 21 . These findings suggest that allergen sensitization may peak during early childhood and decline as children grow older, potentially indicating the development of immune tolerance over time [22][23][24] . The findings of this study are consistent with previous research, which also found that boys are more prone to developing asthma, rhinitis, and eczema 25 .…”
Section: Discussionmentioning
confidence: 90%
“…The initial 1000 days of life play a pivotal role in the development of food allergies, During the period from early pregnancy to childhood, it is essential to prioritize additional observational research and clinical trials 21 . These findings suggest that allergen sensitization may peak during early childhood and decline as children grow older, potentially indicating the development of immune tolerance over time [22][23][24] . The findings of this study are consistent with previous research, which also found that boys are more prone to developing asthma, rhinitis, and eczema 25 .…”
Section: Discussionmentioning
confidence: 90%
“…The risk of bias in randomized controlled trial (RCT) studies was assessed using the Cochrane Collaboration Risk of Bias tool [ 21 ], and the risk of bias in non-RCT trials was assessed using the Risk of Bias in Nonrandomized Studies of Interventions tool [ 22 ]. For all study reports, the summary Tables ( Supplemental Tables 1 and 2 ) [ [8] , [9] , [10] , [11] , [13] , [14] , [15] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] ,…”
Section: Methodsmentioning
confidence: 99%
“…Eleven prospective cohort studies (41,637 participants) [ 15 , 42 , 48 , 77 , [81] , [82] , [83] , [84] , 87 , 89 , 91 ], 2 case-control studies (1142 participants) [ 62 , 86 ], 1 nested case-control study (1128 participants) [ 78 ], 1 cross-sectional study (760 participants) [ 65 ], and 1 cluster-randomized study (1239 participants) [ 26 ] reported on AD. Overall, in both intervention and observational studies, early complementary food introduction did not appear to be associated with the risk of AD (OR, 0.94; 95% CI: 0.88, 1.02; P = 0.13; moderate heterogeneity [I 2 = 47%]), shown in Supplemental Figure 13A .…”
Section: Risk Of Admentioning
confidence: 99%
See 2 more Smart Citations